Examining the Process of Automation Development and Deployment - Barsalou, Edward (University of Waterloo, 2005)
In order to develop a better understanding of the process of development and deployment of automated systems, this thesis examines aspects of project execution and knowledge transfer in the context of a large automation project.
Background issues of project execution are examined, including the challenges of knowledge sharing in project development, as well as a brief discussion of measures of project success. The lifecycle of a large automation project is presented, including aspects of development and the development team, as well as design challenges inherent in the development process of a successful automation project which consisted of approximately 11,000 hours of combined effort by vendor and customer development teams.
Human factors aspects of large automation projects are explored, including an investigation of the workings of a large project team, by examining the cognitive aspects of the project team, as well as ecological aspects of the automation development process.
Using an interview methodology that can be termed the "echo method", project team members were interviewed in order to elicit helpful and unhelpful behaviours exhibited by other team members throughout the project. The results of these interviews are categorized and examined in the context of both knowledge management and social networks. Common themes in interview comments are identified, and related to both the areas of knowledge management and social networks.
Results indicated that team member experience and availability affect overall team performance. However, overlapping capabilities within a team were found to allow the team to adapt to changing circumstances, as well as to overcome weaknesses in team member availability. Better understanding of team interactions and capabilities supports improvements in project performance, ultimately delivering higher quality automation and streamlining the development process.
Keywords: Systems Design; Automation; Social Networks; Human Factors